Kompleks bilal court booking system / Intan Rashidah Rashid - Rashid, Intan Rashidah (2022)
A prototype for the booking system for the badminton and futsal services is provided at Kompleks Bilal Pahi in Kuala Krai, Kelantan, where customers can use the system to make reservations. First, customers have trouble making reservations since there is no system in place. If not, the consumer must contact or WhatsApp to check the court's availability before making a reservation. Because customer reservations are stored in a logbook, staff members also have trouble keeping track of them. There were frequently issues with duplicating booking data. This project's goal is to determine the present business process and issues that users, staff/admins, and the manager of Kompleks Bilal Pahi have with managing the booking process. The Kompleks Bilal Court Booking System makes it simpler and quicker to make reservations. This is due to the system's ability to be used for the booking process. This prototype system's six sequential steps were created utilising the waterfall model. Analysis of requirements, implementation, testing, and documentation are the steps. Additionally, the theory of the Ten Usability Heuristics served as a set of guidelines for the creation of the Kompleks Bilal Court Booking System. A test plan has been set up for the customers, admin and manager to make sure functionality of the system is meets and their feedback has been taken into consideration, all the recommendations and enhancement received during the testing sessions can used as a reference for future work to improve the functionality and usability of the system. The system has passed all the requirements in the test plan. It is hopes that Kompleks Bilal Court Booking System will enhance the currents business process for the customers, admin and manager of Kompleks Bilal Pahi.